A Strategic Approach to Succeed on Clinical Case-Based Multiple-Choice Exams [version 2; peer review: 2 approved] - Christina L. Shenvi; Erin Bakal; Kunal P. Patel; Animesh Jain; Neva Howard; Gita Fleischman; Meredith Niess; Kelly Lacy Smith (MedEdPublish)
Despite the importance of case-based multiple-choice question (CBMCQ) exams, medical educators rarely discuss strategies to systematically approach these questions, and literature on the topic is limited. Through trial-and-error, many students develop more refined and efficient approaches to answering CBMCQs that help them maximize the application of their knowledge base. In this article we present a structured six-step approach to answering CBMCQs, grounded in dual process theory. We provide strategies for success on CBMCQ-based exams and approaches to challenging question types. We also present tips for helping neurodiverse students. Medical educators can use this structured approach and the related tips to coach students on improving performance on CBMCQ-based exams.